Computed Tomography Diagnosis of Nonspecific Acute Chest Pain in the Emergency Department: From Typical Acute Coronary Syndrome to Various Unusual Mimics. Issue 1 (January 2017) - Yoo, Seung Min; Chun, Eun Ju; Lee, Hwa Yeon; Min, Daniel; White, Charles S.
Abstract : It is a challenging task for emergency department physicians to establish a precise and rapid diagnosis based only on clinical and laboratory findings in patients who present with nonspecific acute chest pain. In this circumstance, CT angiography can provide important clues to the diagnosis. To provide a rapid diagnosis of acute coronary syndrome (ACS) and its various mimics, the physician should enumerate each possible cause of acute chest pain on the basis of an objective assessment of pretest probability. On the basis of clinical suspicion, the appropriate CT protocol should then be performed. Moreover, radiologists should be familiar with typical CT findings of ACS and its various mimics to assist the emergency department physician in diagnosing patients with nonspecific acute chest pain. This review article presents an overview on choosing an appropriate CT protocol in patients with nonspecific acute chest pain and provides specific CT findings of ACS and various mimics of ACS.